Якість вищої освіти україни в контексті болонського процесу - Прилипко, С. М.; Клімова, Г. П. (Право, 2014)
Статтю присвячено теоретико-методологічному аналізу якості вищої освіти України з урахуванням європейських стандартів. Проаналізовано умови забезпечення якості вищої освіти. Розглянуто основні напрямки удосконалення системи контролю та оцінки якості вищої освіти України в контексті Болонського процесу. // The article is devoted to the theoretical and methodological analysis of the quality of higher education in Ukraine, taking into account European standards. The conditions for ensuring the quality of higher education are analyzed. The main directions of improvement of the control system and assessment of the quality of higher education in Ukraine in the context of the Bologna process are considered.
Keywords: вища освіта; якість вищої освіти; європейський освітній простір; забезпечення якості вищої освіти; система оцінки якості вищої освіти; higher education; quality assessment of higher education; European educational space